Pengaruh Pertumbuhan Perusahaan, Ukuran Perusahaan, Struktur Kepemilikan, Profitabilitas Dan Leverage Terhadap Kebijakan Dividen Perusahaan (Studi Kasus Perusahaan Manufaktur Yang Terdaftar di BEI 2017-2021) - Wahyuni Lailika; Diana Dwi Astuti; Haifa Haifa (Institut Teknologi dan Sains Mandala, 2023)
Dividend is the proportion of profits or profits distributed to shareholders. The value and time of dividend payment is determined by the General Meeting of Shareholders. In distributing profits to shareholders, a dividend policy is implemented, namely the company will determine whether it will be distributed to shareholders as dividends or will be retained in the form of retained earnings to finance investment in the future. The research aims to determine the effect of company growth, company size, ownership structure, profitability and leverage on dividend policy. The population in this study are manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange in 2017-2021. The sampling technique used in this study was purposive sampling and 15 companies were obtained. The data analysis method used is Multiple Regression Analysis. The results showed that company growth, company size, ownership structure, profitability, and leverage simultaneously influence dividend policy. Company growth, Profitability which is proxied by Return On Assets, Leverage which is proxied by Debt to Equity Ratio partially influences dividend policy. Meanwhile, company size and ownership structure, which are proxied by institutional ownership, partially have no effect on dividend policy.